Lincoln Cathedral in the Reign of Queen Elizabeth I - Walker, R. B. (The journal of ecclesiastical history, 1960)
When the three royal commissioners, doctors Thomas Bentham, William Fleetwood and Stephen Nevinson, visited Lincoln cathedral in September 1559 their injunctions, which were largely copied from those of the Edwardine visitors in April 1548, marked the permanent establishment of reform within the mother church of the diocese. It is well known that at this time they and other commissioners deprived many of the higher clergy who refused to conform to the new settlement; in the diocese of Lincoln only one of the six archdeacons retained office throughout these troubled years and out of the 54 cathedral prebends either 11 or 12 changed hands. Five canons were displaced to allow the restoration of married clerks and another five or six were deprived. In contrast to this all the cathedral dignitaries and canons residentiary remained, although there is strong reason to suspect their secret hostility to protestant reform. Since Matthew Parker had no wish to recover his deanery, Francis Mallet the faithful chaplain of queen Mary whom she and cardinal Pole just before their deaths had intended to elevate to the see of Salisbury, was permitted to retain his office. Previously he had lived at Court and scarcely visited his church but on 17 August 1560 he protested major residence at Lincoln. His conservatism may be inferred from a sermon which he preached in the cathedral, in 1561 or 1562, wherein he declared in favour of there being seven sacraments. Unfortunately only a month previously the cathedral divinity lecturer, the reformer Thomas Godwin, had preached very vehemently in favour of there being two, and no more than two, sacraments. Thereupon William Todd, who was the only strongly protestant residentiary at the time, had appealed to two local gentry, of whom one was Sir. Francis Ayscough, the brother of the martyred Anne Askew, to raise a complaint against Mallet in the Privy Council. But nothing came of this and Mallet was not dislodged.